OPPORTUNITIES AND CHALLENGES OF THE LIBRARIAN PROFESSION IN THE ERA OF GLOBALIZATION - Fauzan, Ashrof Achmad (Academic Solution Publisher, 2024)
Librarian is a profession that is less considered important when compared to other professions. Along with the developing technology librarians face challenges by being able to compete in the globalization era. In facing the challenges of the globalization era, librarians are required to have competence and certification and librarians must have new innovations in order to take advantage of opportunities by using information technology. In this study using the literature study method in journals that discuss the